Digital India Reflections and Practice (Advances in Theory and Practice of Emerging Markets,, 2018)
This book offers a multidisciplinary resource on digital government, while specifically focusing on its role within the emerging market of India. The Government of India (GoI) is concentrating on transforming India under the Digital India initiative. In order to do so, it has emphasized three core areas: (1) Computing infrastructure as a utility to every citizen; (2) Governance and services on demand; and (3) Digital empowerment of citizens. The chapters in this book address issues surrounding these areas, highlighting concepts such as knowledge societies, urban operations and logistics, issues in managing emergent Information Communication Technologies (ICTs), and also smart analytics for urbanization. The chapters contribute to the theory, practice and policy for a "Digital India." The book captures lessons, knowledge, experiences (about challenges, drivers, antecedents, etc.) and best practices emerging from implementation of various projects. While the book is dedicated to a "Digital India," this book can also be valuable resource for public administrators, government officials and researchers in other emerging markets and developing countries in Asia, Africa and Latin America where similar socio-political and economic conditions exist.